ANALISIS YURIDIS ATAS MINYAK KARO DUKUN PATAH PERGENDANGEN SEBAGAI PRODUK INDIKASI GEOGRAFIS KABUPATEN KARO - DIKKI PALMA KACARIBU (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Saidin2. T. Keizerina Devi A3. Jelly Leviza Geographical Indication is a sign indicating the origin of an item and / or a product due to environmental factors. Factor factors or factors that exist. Indication is maintained as a sign indicating the origin of the goods, which is due to environmental factors. Factor, or factor formed. Karo Oil is a traditional oil made by Karo tribe that is mixed traditionally and is well known for its benefits and used long time among the people of North Sumatra. By using any other Intellectual Property Rights of any Intellectual Property Rights on the register of protection may cause the product to become higher, so it can more easily move a product of origin.Keywords: Registration, Protection, Geographical Indication Of Karo Society